2006
DOI: 10.1063/1.2405849
|View full text |Cite
|
Sign up to set email alerts
|

Influence of sputtering pressure on polarity distribution of aluminum nitride thin films

Abstract: The authors have investigated the influence of sputtering pressure on the polarity distribution of aluminum nitride (AlN) films. They have found that sputtering pressure strongly influences the polarity distribution of AlN films prepared on molybdenum electrodes. The polarity distribution of the AlN films was observed by piezoresponse force microscopy. The polarity orientation is decided with respect to each fine grain constituting the AlN films, and polarity conversion from Al polarity to N polarity is observ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 44 publications
(25 citation statements)
references
References 26 publications
1
24
0
Order By: Relevance
“…The pressure dependence of the universal transition region has been studied by a some authors (Fardeheb-Mammeri et al 2008;Kamohara et al 2006;Vashaei et al 2009). Figure 1 shows the FWHM evolution of the rocking curve of the (0002) reflection in A1N films as a function of the process pressure for the four pressures studied, 2, 4, 6 and 8 mTorr.…”
Section: Resultsmentioning
confidence: 99%
“…The pressure dependence of the universal transition region has been studied by a some authors (Fardeheb-Mammeri et al 2008;Kamohara et al 2006;Vashaei et al 2009). Figure 1 shows the FWHM evolution of the rocking curve of the (0002) reflection in A1N films as a function of the process pressure for the four pressures studied, 2, 4, 6 and 8 mTorr.…”
Section: Resultsmentioning
confidence: 99%
“…4 Meanwhile, it was reported that the polarity orientation distribution of piezoelectric films can also influence their piezoelectric response. 5 Grains with metal polarity and those with oxide polarity show different piezoelectric properties. The macroscopic piezoelectric response of the films is the result of the polarity orientation distribution.…”
Section: Introductionmentioning
confidence: 99%
“…Piezoresponse force microscopy (PFM), originally used to detect domain structures, polarization switching, and for local hysteresis spectroscopy in ferroelectric materials, [7][8][9] has been extended to characterize piezoelectric semiconductors, such as GaN, 10,11 AlN, 3,5 and ZnO. 1,[12][13][14][15] Several investigations on piezoelectric properties of nanostructures 1,14 and films 12,13 have been carried out with PFM recently, including determination of piezoelectric coefficient 12 and observation of spontaneous polarization and inversion domains.…”
Section: Introductionmentioning
confidence: 99%
“…As AlN exhibits piezoelectric property along its c-axis, AlN films for BAW resonators should be c-axis orientated and the fabrication conditions for c-axis deposition have been investigated. It is generally known that the texture of bottom electrode influences the preferred orientation of following AlN and (111) plane of face centered cubic (fcc) and (110) of body centered cubic (bcc) enhance the c-axis texturing [1,2]. Thus, it is essential to fabricate strongly oriented bottom metal layer.…”
Section: Introductionmentioning
confidence: 99%